Terceira contribuicäo ao conhecimento do gênero Archytas Jaennicke, 1867: (Diptera, Tachinidae) - José Henrique Guimarães (Memorias do Instituto Oswaldo Cruz, 1961)
Twelve species of the genus Archytas Jennicke, 1867, eight of which described as new are studied and figured in detail. Definitions of the species are based mainly on characters of male genitalia. The male genital characters are the most significant for separation of the species and most demonstrative of their affinities. By examining a long series of species of this genus we came to the conclusion that the presence of one pair of median marginal bristles on the third abdominal tergite seems to be characteristic of the genus. This caracter apparently so important, is not however considered fundamental. The most significant example is found in Archytas lenkoi sp. n. and Archytas vexor Curran, 1928. In A. lenkoi we can find one or two pairs or thay may, less frquently, be absent. In A. vexor these bristles are lacking. The shape of the male copulatory apparatus of Jurinia nitidiventris Curran, 1928 refered to by CURRAN in his "Revision of Archytas", is not characteristic of any species of the group and so, is not considered in this paper. To help in the identification, the species studied here are divided into groups. The analis group" includes: A. apicifer (Walker, 1894), A. californiae (Walker, 1856), A. nivalis Curran, 1928, a. giacomellii (Blanchard, 1941), A. basifulvus (Walker, 1849), A. incasanus Townsend, 1912 and A. cirphis Curran, 1927. The identification of members of these group is extremely difficult owing both to their similarity in colour pattern and to their variability. They all have black testaceous or dark brown abdomen, the last segment pale or brownish pollinose; second segment without bristles; third with a pair of strong marginals, fourth and fifth with two rows of discals on apical third. The final determination often rests upon the structure of the male copulatory apparatus. Fortunately in this group, many of the forcipes superiores and palpi genitalium are strikingly different from one another. The "zikani group" includes: A. zikani sp. n., A seabrai sp. n., A. duckei sp. n. and A. vernalis Curran, 1928. This group may be characterized as follows: forcipes interiores absent; forcipes superiores strongly chitinized an dilated at anex. Within this group, the forcipes of. A. seabrai sp. n. do not present an aberrant form. The "dissimilis group" will be studied in forthcoming papers. The limits of the genus Archyta Jaen. are not as yet sharply difined, the evaluation of the significance of each character used in the definition remaining as most difficult problem. The distinction between Archytas and other related genera is very difficult, chiefly because it is based on variable characters. In this paper we place the genera Parafabricia Towsend, 1931, Itachytas Blanchard, 1940, Archynemochaeta Blanchard, 1941, Proarchytoides Blanchard, 1941 and Archytodejeania Blanchard, 1941 in the synonymy of Archytas Jaen. The detailed examination of the characters used in their definition, proved them to be fundamentally proposed on basis of chaetotasy, these characters alone being precarious, because of the considerabel intraspecifical variation. The type of the new species are in the Oswaldo Cruz Institute collection. Rio de Janeiro, Brazil, and paratypes in the collections of the followings institutions: Departamento de Zoologia da Secretaria de Agricultura do Estado de São Paulo; Instituto de Ecologia e Experimemtação Agrícolas; Departamento de Defesa Sanitária Vegetal; Campos Seabra collection; and Barbiellini collection.